The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2015
DOI: 10.1007/s11135-015-0297-7
|View full text |Cite
|
Sign up to set email alerts
|

The level of socioeconomic development of EU countries and the state of ISO 14001 certification

Abstract: This study examines the relationship between the level of socioeconomic development of the EU 28 countries and the adoption of International Organization for Standardization (ISO) 14001 environmental management system. First, through a multivariate comparative analysis of the secondary data obtained from the public statistics, a Hellwig’s synthetic indicator is created to rank the level of socioeconomic development of the EU 28 countries. Then, using the total number of certificates issued in 2012 and the incr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
23
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 37 publications
(25 citation statements)
references
References 35 publications
(41 reference statements)
2
23
0
Order By: Relevance
“…Our study revealed that more visible forms of self-regulation are more effective. In the broader sense, our results confirm those gained in the studies conducted by Ferro [37], Fura and Wang [38], Goedhuys and Sleuwaegen [41], and Masakure and coauthors [39], to the effect that companies from less developed countries view certification as more important than those from more developed countries. Although our study provides evidence that companies with multinational ownership and export activity are more likely to have ISO 9001 and ISO 14001 certification, our results showed that the internationalization (multinational ownership and export activities) of the company does not influence the level of performing environmental practices.…”
Section: Discussionsupporting
confidence: 89%
See 1 more Smart Citation
“…Our study revealed that more visible forms of self-regulation are more effective. In the broader sense, our results confirm those gained in the studies conducted by Ferro [37], Fura and Wang [38], Goedhuys and Sleuwaegen [41], and Masakure and coauthors [39], to the effect that companies from less developed countries view certification as more important than those from more developed countries. Although our study provides evidence that companies with multinational ownership and export activity are more likely to have ISO 9001 and ISO 14001 certification, our results showed that the internationalization (multinational ownership and export activities) of the company does not influence the level of performing environmental practices.…”
Section: Discussionsupporting
confidence: 89%
“…In developing countries, "companies increasingly use management certification to overcome reputation problems and enter international markets" [35]. Several studies confirm that companies from less developed countries have a higher interest in certification than those from more developed countries [37][38][39][40]. Based on data pertaining to manufacturing companies operating in 59 countries, Goedhuys and Sleuwaegen [40,41] found that the signaling effects of international standards certification are stronger in developing and transitional countries and that companies operating domestically perceive certification as a "surrogate institutional mechanism which helps them to export".…”
Section: Introductionmentioning
confidence: 99%
“…For this purpose, the prototype of the proposed method, HDI, cannot be used, because some aspects of this index are characterized by only one indicator.8 The strategy sets targets for all indicators that should be implemented by individual countries as well as the entire EU. Therefore, none of the indicators can be omitted in the construction of a composite indicator.9 The presented results may differ significantly from other studies on socio-economic development of the EU owing to the use of specific indicators(Fura-Wang 2017).10 Because of this specific method of normalization, the results obtained are relative. Therefore, it is worth confronting them with results obtained on the basis of other types of normalization.…”
mentioning
confidence: 75%
“…Regional development is a multi-faceted process that cannot be measured and described with a single parameter. Complex phenomena are analysed with the use of synthetic variables where numerous indicators are expressed by a single synthetic variable (Milenkovic et al 2014;Holgado Molina et al 2015;Pérez et al 2015;Ding et al 2016;Fura and Wang 2017).…”
Section: Methodsmentioning
confidence: 99%